Titanium Reconstruction Nailing For Sub - Trochanteric Fractures of Femur - Kumar Jose, Ashish; Kumar R., Surendher; R, Krishnagopal; MMR, Sandeep (International Journal of Medical Research and Review, 2015)
Introduction: Sub-trochanteric fractures of femur present a challenging situation to the orthopaedic surgeons world-wide. Complications like malunion, nonunion and implant failure are high. Several implants have been designed for fixation of sub-trochanteric fractures. In this study we analyze the functional and radiological outcome of sub-trochanteric fractures treated by Titanium Reconstruction nails. Methods: This is a prospective study. 20 patients with sub-trochanteric fractures treated by Titanium reconstruction nail from June 2012 to December 2014 were included in the study. We analyzed these 20 patients for functional and radiological outcome and complications. Results: The fracture union rate was 100 % and the average union time was 14 weeks. 3 patients had varus malunion and shortening was noted in 4 patients. 85% of the patients had excellent to good functional outcome. Conclusion: We concluded that Titanium Reconstruction nail is an ideal implant for sub-trochanteric fractures with an excellent union rate and a very good functional outcome.